DAMPAK POTENSIAL AUDIT KINERJA TERHADAP PENINGKATAN PELAYANAN PUBLIK POLITEKNIK NEGERI BANDUNG - Ahmad Syarief – Politeknik Negeri Bandung (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2017)
Activity pemerintaterhadap public service agencies have been less mememuaskan both in the fields of education, health and other fields it is caused by many governments cope faktor.Untuk always conduct an audit of the performance (activity) conducted by Government agencies in carrying out his ministry. This study aims to examine the level of public services provided by POLBAN as an institution engaged in education. With the internal and external audit whether the service had to be increased, stable or decreasing of statistical test study can see the progression.